External Factors and Capital Structure - ZIA UR REHMAN; SHER ALI KHAN; ASAD KHAN (Journal of Business & Tourism, 2021)
Financing decisions and its effect on firm value continues to attract the attention of the researchers and have explore several internal and external factors that influence the financing decisions of the firm and how it affects firm value. The aim of the study is to examine the effect of external factors on the financing decisions of the listed nonfinancial firms of Pakistan; the empirical findings of the study reveal that external factors do influence the financial decisions of the firm. GDP growth rate, corporate taxes, banking sector development and development of stock markets significantly influences the financing decisions of the firms. On the other hand we find weak relationship between corruption, real interest rate and leverage. Moreover, the relationship between GDP growth rate, corporate taxes, development of stock markets, banking sector development, real interest rate and leverage is positive whereas in case of corruption it is negative.